1991
DOI: 10.1073/pnas.88.8.3238
|View full text |Cite
|
Sign up to set email alerts
|

Production of site-selected neutralizing human monoclonal antibodies against the third variable domain of the human immunodeficiency virus type 1 envelope glycoprotein.

Abstract: Cell lines secreting IgG1 human monoclonal antibodies (mAbs) to the envelope glycoprotein, gpl2O, of human immunodeficiency virus (IRV) have been produced by transformation of peripheral blood cells front IIV-infected individuals and by fusion of transformed cells to a humanmouse heteromyeloma cell line (SHM-D33). Two human mAbs were site-selected by means of a 23-mer synthetic peptide spanning a portion of the third variable domain of gpI20 from the MN strain of HIV. The two heterohybridomas produce three tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(137 citation statements)
references
References 49 publications
2
135
0
Order By: Relevance
“…To determine whether the mAb YZ23 epitope overlaps previously reported neutralizing epitopes, we measured the ability of mAb YZ23 to inhibit binding of gp120 (MN strain) by the following reference mAbs: IgG b12 directed to a CD4BS epitope not involving residues 421-433 (60, 61); mAb 2G12 to a conformational carbohydrate-dependent epitope (62,63); mAbs 17b and 48d to a CD4-inducible epitope exposed upon gp120 binding to sCD4 (64,65); and mAb 447-52D to the conserved V3 apex epitope (66,67). These mAbs neutralize some but not all strains within and across group M HIV subtypes (60, 68 -70).…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the mAb YZ23 epitope overlaps previously reported neutralizing epitopes, we measured the ability of mAb YZ23 to inhibit binding of gp120 (MN strain) by the following reference mAbs: IgG b12 directed to a CD4BS epitope not involving residues 421-433 (60, 61); mAb 2G12 to a conformational carbohydrate-dependent epitope (62,63); mAbs 17b and 48d to a CD4-inducible epitope exposed upon gp120 binding to sCD4 (64,65); and mAb 447-52D to the conserved V3 apex epitope (66,67). These mAbs neutralize some but not all strains within and across group M HIV subtypes (60, 68 -70).…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that Re-LPS inhibited binding of fluorescently labeled gp120 to the surface of the H9 cells (Fig. 5A) similarly to anti-gp120 monoclonal antibodies 257-D IV or 268-D IV (45), which react with the HIV-1 MN V3 epitope KRIH or HIGPGR (data not shown).…”
Section: Inhibition Of Binding and Viral Attachment To Cells By Lps-mentioning
confidence: 93%
“…Many HIV-1-neutralizing human monoclonal antibodies (nhmAbs) have been identified by immortalization of B lymphocytes from HIV-infected patients eitherby EBV transformation (Gorny et al, 1989;Robinson et al, 1990) or by cell fusion (Grunow et al, 1988;Buchacher et al, 1994) (hybridomas obtained by fusion of EBV transformants with heteromyeloma cells have also been extensively used (Posner et al, 1987;Gorny et al, 1991;Posner et al, 1991)] followed by screening of their supernatants for antigen-specific antibodies. Selection of HIV-1-neutralizing antibodies from phage-displayed human antibody libraries has also been used by panning against one antigen (Burton et al, 1991) or several antigens sequentially ; it is a powerfull and versatile approach that allows modifications of the panning process for enhanced selection of antibodies with desirable properties (Zhang and Dimitrov, 2006, in press).…”
Section: Introductionmentioning
confidence: 99%